2014
DOI: 10.3390/s140815415
|View full text |Cite
|
Sign up to set email alerts
|

A Kalman Filter-Based Short Baseline RTK Algorithm for Single-Frequency Combination of GPS and BDS

Abstract: The emerging Global Navigation Satellite Systems (GNSS) including the BeiDou Navigation Satellite System (BDS) offer more visible satellites for positioning users. To employ those new satellites in a real-time kinematic (RTK) algorithm to enhance positioning precision and availability, a data processing model for the dual constellation of GPS and BDS is proposed and analyzed. A Kalman filter-based algorithm is developed to estimate the float ambiguities for short baseline scenarios. The entire work process of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 11 publications
2
37
0
Order By: Relevance
“…The error of each satellite is assumed to be independent of each other. With the weighted least squares (WLS) estimation, the receiver states can be estimated using (4).…”
Section: Fault Detection Based On Consistency Checkmentioning
confidence: 99%
See 1 more Smart Citation
“…The error of each satellite is assumed to be independent of each other. With the weighted least squares (WLS) estimation, the receiver states can be estimated using (4).…”
Section: Fault Detection Based On Consistency Checkmentioning
confidence: 99%
“…Global positioning system (GPS) sensor provides absolute localization service in all outdoor areas in all weather conditions [3]. In open-sky areas, GPS sensor can achieve up to sub-meter positioning accuracy if differential correction is available [4,5]. However, particularly in Asian highly-urbanized city, dense skyscrapers and narrow streets strongly challenge the GPS localization performance in two aspects, blockage and reflection [6].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the introduction or exclusion of an ascending or descending satellite, of low elevation angle and/or low Signal-to-Noise ratio (SNR) may lead to a jump in the position time series. Likewise jumps are present when moving from fixed to float solution of the ambiguity resolution in sequent durations, as the new measurements introduce an inconsistency into the Kalman filter solution [15]. These jumps, which affect more the vertical than the horizontal components, can be removed by excluding certain satellites of lower SNR during the periods when jumps are present; This lead to improve the STD of Up component to be 2.5mm.…”
Section: Availability and Precision At The China Sitementioning
confidence: 99%
“…The combination of two or more satellite systems offers more visible satellites to users, and that will enhance the satellite geometry with the expectation of improving the overall positioning solution [12,13]. A number of studies have generally shown that the contribution of combined GNSS systems improves the positional accuracy and increases the rate of fixing ambiguity resolution [14,15]. For instance, Cai and Gao [16] have indicated an improvement in the positional accuracy when combining simulated GPS and GLONASS observations as compared to GPS-only solution.…”
Section: Introductionmentioning
confidence: 99%
“…The carrier phase measurement observed by the two receivers at a certain epoch can be written as [35]: ϕb,ki=λk1(rb,kiIb,ki+Tb,ki)+fk(δtb,kdtki)+Nb,ki+εb,ki ϕr,ki=λk1(rr,kiIr,ki+Tr,ki)+fk(δtr,kdtki)+Nr,ki+εr,ki where ϕ is the carrier phase measurement (unit: cycle), λ is the carrier wavelength (unit: m), r represents the true geographical distance between the satellite and the receiver (unit: m), I is the ionospheric delay (unit: m), T is the tropospheric delay (unit: m), f is the carrier frequency (unit: Hz), δt is the receiver clock error (unit: s), dt is the satellite clock error (unit: s), N is the integer ambiguity (unit: cycle) and ε is the residual errors mainly including carrier phase noise and multipath (unit: cycle). Subscripts b and r respectively represent the base and the rover receiver.…”
Section: Dual Frequency Carrier Phase Error Difference Checking Almentioning
confidence: 99%